Satellite and statistical system for advanced river flow prediction - Arias Velásquez, Ricardo Manuel (2022)
Prediction of the river flow, irradiance and wind velocity is a challenge for all the countries to improve the natural resources, the uses of the satellite and meteorological data allow to improve the statistical processing, in this research article a new methodology is proposed for the river flow forecasting in Lima, it is associated to the Transandean tunnel with the watershed of the Atlantic and Pacific ocean. with the basins of Tamboraque, Sheque and Tulumayo. Our findings are the implementation of river flow prediction with the data from 2016 to 2022 with an hourly data, the forecasting allows to obtain information from the satellite data of ambient temperature, rainfall precipitation, wind velocity and atmospheric pressure and evaluated river flows in three basins, with the MAE and RMSE metrics evaluation, it is Tamboraque (3.63 m/s and 5.55), Sheque (0.92 m/s and 1.29 m/s) and Tulumayo (5.28m/s and 11.28 m/s), these technology could be used for the hydroelectric and water supply companies. La predicción del caudal de los ríos, la irradiación y la velocidad del viento constituyen un reto en todos los países para mejorar los recursos naturales. Los usos de los datos satelitales y meteorológicos permiten mejorar el procesamiento estadístico. En este artículo de investigación se propone una nueva metodología para la predicción del caudal de los ríos en Lima, la cual se asocia con el túnel transandino y con las cuencas de los océanos Atlántico y Pacífico. así como con las de Tamboraque, Sheque y Tulumayo. Nuestros hallazgos son la implementación de la predicción de caudales fluviales con los datos de los años 2016 al 2022 mediante un dato horario. El pronóstico permite obtener información de los datos satelitales de temperatura ambiental, precipitación pluvial, velocidad del viento y presión atmosférica. Se evaluaron los caudales fluviales en tres cuencas, con la evaluación de las métricas MAE y RMSE, Tamboraque (3. 63 m/s y 5,55), Sheque (0,92 m/s y 1,29 m/s) y Tulumayo (5,28m/s y 11,28 m/s). Esta tecnología puede ser utilizada por las empresas hidroeléctricas y de abastecimiento de agua.